FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DISMENORE PADA SISWI SMA NEGERI 2 MEDAN TAHUN 2014 - Deby Shinta O. Sirait; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT Dysmenorrhea is lower abdominal pain that is felt just before or during menstruation that can interfere with daily activities. The prevalence of dysmenorrhea in Indonesia in 2008 was 64.25%. The purpose of this research was to determine the factors associated with the incidence of dysmenorrhea in female students of SMAN 2 in 2014. This research is an observational study with cross sectional approach. Sample was many 128 students were taken by simple random sampling. The research instrument used was a questionnaire as well as the scales of measuring instruments and gauges. Univariate data were analyzed descriptively and bivariate data were analyzed using the chi-square test with 95% confidence level (α = 0.05). The results of the research shown that proportion prevalence of dysmenorrhea in SMAN 2 in January to August 2014 was 85.90% with mild pain intensity 79.10%, moderate pain 8.20%, and severe pain 12.70%. The highest proportion of the dysmenorrhea of the respondent at category ages 14-15 years olds (86.00%), age of menarche ≤ 12 years old (87.70%), longer menstrual <7 days (86.30%), normal menstrual cycles (87 , 40%), frequency of exercise (96.90%), overweight (100.00%), and no family history (90.50%). The result of bivariate analysis, there is a significant association between exercise habits (p = 0.040) and family history (p = 0.001). There was no significant correlation between age,, age of menarche, duration of menstruation, the menstrual cycle, and nutritional status. It is suggested to SMA Negeri 2 field for exercise regularly. For those girls who have a history of dysmenorrhea and dysmenorrhea in a family to see a doctor to prevent other endometris. Keywords: Dysmenorrhea, Risk Factors